Air and Steam Gasification of Almond Biomass - McCaffrey, Zach; Thy, Peter; Long, Michael; Oliveira, Melina; Wang, Li; Torres, Lennard; Aktas, Turkan; Chiou, Bor-Sen; Orts, William; Jenkins, Bryan M. (Frontiers in Energy Research, 2019)
Experiments were performed to characterize the gasification products of almond shells removed in nut processing operations and to determine the effect of gasifying media on bed agglomeration. Agglomeration in the reactor bed due to reactions between the flue gas and the bed medium was significantly worse under air gasification than under steam gasification. The higher heating value during air gasification of almond biomass ranged from 4–6 MJ kg-3, whereas gas concentrations ranged from 14%–18% H2, 3–4% CH4, 43– 50% N2, 16 – 19% CO, and 16 –17% CO2. For steam gasification, higher heating value was 10–12 MJ kg-3 and gas concentrations were 35–40% H2, 5 – 7% CH4, 17 – 21% N2, 18 – 21% CO, and 16 – 18% CO2. The high level of potassium in the almond shells led to strong corrosion of the bed material due to flue gas transport of potassium compounds. As a result of long duration and elevated temperature approaching 1000 oC, potassium together with silica are mainly transported as aerosol melt particles that form an adhesive resulting in enhanced agglomeration.